SAT0400 Clinical Factors Impacting Statin Usage in A Longitudinal Ankylosing Spondylitis Cohort. (15th July 2016) - Dau, J.; Weisman, M.; Lee, M.; Ward, M.; Brown, M.; Diekman, L.; Rahbar, M.; Gensler, L.; Reveille, J.
Abstract : Background: Patients with ankylosing spondylitis (AS) are at higher risk for developing cardiovascular comorbidities. While aortic valve and conduction defects are most common, increased levels of LDL cholesterol are also seen. Statin usage has been reported to lower CRP and ESR though the power of these studies are limited due to small sample size and short-term follow-up (1, 2). Objectives: This study examines associations of statin usage with socio-demographic and clinical factors, including disease activity, functional impairment, and radiographic severity in patients with two years of follow-up or more. Methods: 655 AS patients meeting modified New York criteria followed at least 2 years (and up to 12 years) were included in the analysis. Demographic and clinical parameters (disease activity and functional impairment were collected every 6 months, as well as radiographic assessments (BASRI and mSASSS) every 2 years. Univariable and multivariable mixed effect models were developed to identify independent factors associated with statin usage over time. Results: Mean disease duration was 18 years (SD=13). 10% (n=66) of the cohort were using statins. Univariable longitudinal regression models are shown below: Multivariable longitudinal analyses controlling for confounders showed independent associations of age >40 years (p<0.001, OR=5.5 (2.3, 13.3)), the presence of cardiovascular disease (p<0.001, OR=7.6 (3.8, 15.5)), diabetes (p=0.01, OR=4.7 (1.4, 15.4)), opiate use (p=0.03, OR=2.0 (1.1, 3.7)), and CRP (p=0.03, OR=0.4 (0.2, 0.9)). Conclusions: Statin usage was, as expected, more likely in those of older age with greater disease duration and greater radiographic severity. Even though statins are known to reduce CRP, the association with markers of lower disease activity, both subjective (BASDAI on univariable analysis) and objective (CRP on both univariable and multivariable analyses), raises the possibility of a role in suppressing inflammation in patients with AS. References: Heinemann S and Daemen M. Cardiovascular risks in spondyloarthropaties. Curt Opin Rheumatol. 2007 19:358–362. Denderen JC, Peters MJL, van Halm VP, van de Horst-Bruinsma, Dijkmans BAC, Nurmohamed MT. Statin therapy might be beneficial for patients with ankylosing spondylitis. Ann Rhem Dis. 2006; 65: 695–696. Disclosure of Interest: J. Dau: None declared, M. Weisman Grant/research support from: UCB, Human Genome Sciences, Sanofi, Eli Lilly and Co, Genentech, Inc., Santarus Inc., EMD Serono, ChemoCentryx, GSK, Immunomedics Inc., Consultant for: Boehringer Ingelheim/Proskauer, Ardea Biosciences, Epirus Biopharmaceuticals, Acerta Pharma, M. Lee: None declared, M. Ward: None declared, M. Brown: None declared, L. Diekman: None declared, M. Rahbar: None declared, L. Gensler: None declared, J. Reveille: None declared